P.Romanova romāna "Biedrs Kisļakovs" inscenējums uz Rīgas Krievu Drāmas teātra skatuves. - Kauhova, Jūlija (Latvijas Universitāte, 2012)
Maģistra darbs „P.Romanova romāna "Biedrs Kisļakovs" inscenējums uz Rīgas Krievu Drāmas teātra skatuves” tiek veltīts literāra darba inscenējuma fenomenam, kas sākotnēji nebija paredzēts iestudējumam uz teatrālas skatuves. Maģistra darbā ir apskatīti episka, dramatiska un teatrāla darba īpatnības, ka arī jēdziens „inscenējums”. Balstoties uz romanu P.Romanova "Biedrs Kisljakovs” un R.Ungerna lugas „Trīs pāri zīda zeķes” ir atklāti sacerējuma prozas inscenējuma veidi un metodes, kas ļāva redzēt inscenējuma transformāciju patstāvīgā daiļdarbā.

The Master's research paper “A Production of the Novel Comrade Kislyakov by P. Romanov on the Stage of the Riga Theatre of Russian Drama” is dedicated to the phenomenon of dramatisation of the literary work which originally was not designed to the staging. In the present research paper the special features of theater, epic and dramatic literary works as well as the concept of “staging” are examined in detail. On the material of the novel "Comrade Kislyakov" by Panteleimon Romanov and Rudolf Ungern's play 'Three pairs of silk stockings” the means and ways of dramatisation of a narrative literary work are singled out; this allowed to see the transformation of the dramatisation into an independent work of fiction.
A Production of the Novel "Comrade Kislyakov" by P. Romanov on the Stage of the Riga Theatre of Russian Drama.
Keywords: Filoloģija